2015
DOI: 10.1007/s12020-015-0666-y
|View full text |Cite|
|
Sign up to set email alerts
|

Testosterone stimulates glucose uptake and GLUT4 translocation through LKB1/AMPK signaling in 3T3-L1 adipocytes

Abstract: Decreases in serum testosterone concentrations in aging men are associated with metabolic disorders. Testosterone has been reported to increase GLUT4-dependent glucose uptake in skeletal muscle cells and cardiomyocytes. However, studies on glucose uptake occurring in response to testosterone stimulation in adipocytes are currently not available. This study was designed to determine the effects of testosterone on glucose uptake in adipocytes. Glucose uptake was assessed with 2-[(3)H] deoxyglucose in 3T3-L1 adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…For example, DDT/DDE (191) and some PCBs (344) have been reported to act as AR antagonists. Testosterone has been shown to stimulate glucose uptake in adipocytes (271). Additionally, a positive correlation between insulin sensitivity and testosterone levels has been reported in males (321).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…For example, DDT/DDE (191) and some PCBs (344) have been reported to act as AR antagonists. Testosterone has been shown to stimulate glucose uptake in adipocytes (271). Additionally, a positive correlation between insulin sensitivity and testosterone levels has been reported in males (321).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…[97][98][99][100] In adipocytes, it was confirmed that this regulation occurs through liver kinase B1/AMPK signaling. [97][98][99][100] In adipocytes, it was confirmed that this regulation occurs through liver kinase B1/AMPK signaling.…”
Section: Insulin-dependent Glut 4 Transporter In Pca: a Link Between mentioning
confidence: 99%
“…In the general population, a clear relationship between the serum testosterone concentration and insulin sensitivity has been reported . Low testosterone levels are associated with increased insulin resistance, and the onset of insulin resistance may be influenced by testosterone levels .…”
Section: Postinfertility Management: Diagnosis Of Ks Is a Proxy Of Gementioning
confidence: 99%